The antinematicidal activity of vitamin E and its derivatives on Sterinernema feltieae - Khairan, Khairan; Idroes, Rinaldi; Murniana, Murniana; Diah, Muhammad (Journal of Carbazon, 2023)
Vitamin E is found naturally in some foods, and also available as a dietary supplement. "Vitamin E" is the fat-soluble compounds with distinctive antioxidant activities. The vitamin E acts as an antioxidant, which protects cell membranes. Sterinernema feltieae was selected as a test organism is because this organism is a complex organism and can be used as a model for whole organisms. The objective of this study is to evaluate the activity of vitamin E and its derivatives on Sterinernema feltieae. The results showed that the derivative of vitamin E (C37H55NO3) was most active against S. feltiae with the LD50 value was 207.77 M, followed by vitamin E (C29H50O2) with the LD50 value was 209.09 M. These results indicated that derivative of vitamin E (C37H55NO3) exerts more potent toxicity than vitamin E against Sterinernema feltieae.